Influence of reactor temperature conditions on the recycle flow rate - S. L. Nazanskiy; A. V. Solokhin (Тонкие химические технологии, 2019)
Objectives. The problem of optimizing chemical flow sheets according to energy costs associated with recycling flows is at present quite relevant. The current article investigates the influence of temperature conditions on the recycle flow rate, securing the specified conversion of the recycled flow sheet “reactor – separation unit.”Methods. The study’s main method is the mathematical simulation of a recycled flow sheet based on material balance and chemical kinetics equations. This model assumes that the separation unit can form the recycle and outlet flows of any specified compositions.Results. The mathematical model recycle flows provides the full reagent conversion of recycled flow sheet depends on the reactor type and the temperature conditions in it. It was established that the dependence of the recycle flow rate on the reactor temperature for endothermic reactions has monotonously decreasing shape. The most interesting are exothermic reactions for which the dependence of the recycle flow rate on the reactor temperature curve has a minimum. It is proved that the “reactor – separation unit” system with the plug flow reactor has lower optimal recycle flow rate than the recycled system with the continuous stirred tank reactor. For the adiabatic reactor the dependence of total conversion recycle flow rate on the inlet reactor temperature was investigated. It has been proven that the optimal recycle flow rate is equal to the minimum recycle flow rate for total conversion in the “reactor – separation unit” system.Conclusions. It has been established that isothermal operation conditions are the best in terms of the recycle flow rate, securing the specified conversion for the system.